NTCU induced pre-malignant and malignant stages of lung squamous cell carcinoma in mice model - Muhammad Asyaari Zakaria (Nature Portfolio, 2021)
Abstract Mice have served as an excellent model to understand the etiology of lung cancer for years. However, data regarding dual-stage carcinogenesis of lung squamous cell carcinoma (SCC) remain elusive. Therefore, we aim to develop pre-malignant (PM) and malignant (M) lung SCC in vivo using N-nitroso-tris-chloroethylurea (NTCU). BALB/C mice were allotted into two main groups; PM and M groups which received treatment for 15 and 30 weeks, respectively. Then, the mice in each main group were allotted into three groups; control, vehicle, and cancer (n = 6), which received normal saline, 70% acetone, and 0.04 M NTCU by skin painting, respectively. Histopathologically, we discovered a mix of hyperplasia, metaplasia, and dysplasia lesions in the PM group and intracellular bridge; an SCC feature in the M group. The M group was positive for cytokeratin 5/6 protein which confirmed the lung SCC subtype. We also found significantly higher (P < 0.05) epithelium thickness in the cancer groups as compared to the vehicle and control groups at both the PM and M. Overall, this study discovered that NTCU is capable of developing PM and M lung SCC in mice model at appropriate weeks and the vehicle group was suggested to be adequate as control group for future research.